A facile method to enhance the electrical conductivity of a pure carbon nanotube film. (19th December 2016) - Zhang, Jinling; Liu, Juncheng; Li, Jiao; Ding, Rui
Abstract: A facile method was used to enhance the electrical conductivity of a pure carbon nanotube film, in which a high-voltage direct current electric field was applied to the disc of the spin-coating machine vertically. The effects of the high-voltage electric field on the film's structure and properties were investigated. The film's structure was investigated with Fourier transform infrared spectroscopy and scanning electron microscopy. Its electrical conductivity and visible light transmittance were determined with a Hall effect measurement system and UV–visible spectroscopy, respectively. The results showed that the electrical conductivity of the carbon nanotube film increased about 10-fold when the electric field intensity increased from 0 to 350 kV/m. Furthermore, its transmittance decreased only a little, by about 3%. The possible reason is that the high-voltage electric field had the carbon nanotubes oriented and aligned perpendicular to the substrate to some extent.